Limonene removal using a horizontal-flow anaerobic immobilized biomass bioreactor - Rodrigues, Brenda Clara Gomes [UNESP]; de Mello, Bruna Sampaio [UNESP]; da Silva, Bianca Ferreira [UNESP]; Pozzi, Eloisa; de Lima Gomes, Paulo Clairmont Feitosa [UNESP]; Sarti, Arnaldo [UNESP] (Elsevier, 2021)
In Brazil, a large amount of liquid wastewater generated during orange juice production has a significant negative impact on the citric industries. The treatment of this wastewater has been carried out in biological treatment plants. However, low organic removal efficiency has been achieved while using anaerobic or/and aerobic processes probably due to biological inhibition by toxic compounds like limonene. In this context, the objective of this study was to evaluate the limonene removal by a bench-scale horizontal-flow anaerobic immobilized biomass (HAIB) bioreactor (12L) and the transformation products formed during the applied treatment. The bioreactor was filled with three different matrices (mineral coal, polyurethane foam and gravel) containing immobilized anaerobic sludge. The used substrate contained chemical oxygen demand (COD) of 480 to 1251 mg L−1 and the concentrations of limonene ranging from 10 (period I) to 500 mg L−1 (period X) were monitored by GC–MS. The HAIB bioreactor removed organic matter (>60%), and limonene was removed with high efficiency (>95%), while operated at hydraulic retention time (HRT) of 48 and 24 h.
Keywords: Horizontal-flow anaerobic immobilized biomass bioreactor; Inert media support; Limonene; Transformation products